Polyamide resin composition and polyamide molded body

A polyamide resin composition with specific dicarboxylic acid and diamine components, combined with a controlled copper-based stabilizer, addresses the strength reduction issue, maintaining tensile strength in high-temperature environments.

KR103044550B1Active Publication Date: 2026-11-05MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020247022685
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-12
Filing Date
2023-01-06
Publication Date
2026-11-05
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The addition of copper-based heat stabilizers to polyamide resin compositions reduces the tensile strength, particularly in high-temperature environments, and there is a need for a polyamide resin composition that maintains tensile strength over time in such conditions.

Method used

A polyamide resin composition comprising specific ratios of dicarboxylic acid and diamine components, including a component unit derived from an aromatic or dicyclic dicarboxylic acid and an alkylene diamine with a cyclic structure, along with a controlled amount of a copper-based heat stabilizer, to enhance heat resistance and maintain tensile strength.

Benefits of technology

The composition effectively suppresses the decrease in tensile strength caused by copper-based stabilizers and maintains mechanical strength in high-temperature environments, ensuring long-term durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024073511995-PCT00005_ABST
    Figure 112024073511995-PCT00005_ABST
Patent Text Reader

Abstract

The polyamide resin composition comprises a polyamide resin and a copper-based heat stabilizer. The copper content of the copper-based heat stabilizer is 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin. The polyamide resin comprises a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine. The component unit (a) derived from a dicarboxylic acid comprises a component unit derived from an aromatic dicarboxylic acid or a dicyclic dicarboxylic acid, and the component unit (b) derived from the diamine comprises a component unit (b2) derived from a diamine represented by formula (1), which is 10 mol% or more and less than 50 mol% with respect to the total molar amount of the component unit (b) derived from the diamine.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a polyamide resin composition and a polyamide molded article. Background Technology

[0002] Since conventionally, polyamide resin compositions have excellent moldability, mechanical properties, and chemical resistance, so they are widely used as materials for various parts for medical, industrial materials, automobiles, electrical and electronic, and industrial applications.

[0003] Various additives are added to polyamide resin compositions used for these applications to express characteristics according to each application. For example, it is known that copper-based heat stabilizers are added to improve the heat aging resistance of polyamide resin compositions. For example, Patent Document 1 describes that by adding a copper-based heat stabilizer, the time until the tensile strength is halved when heat-treated at 180°C can be extended to several hundred hours.

[0004] In addition, attempts are being made to change the physical properties of polyamide resins by changing the raw materials of the polyamide resins. For example, Patent Document 2 describes using bis-aminomethyl-norbornene as the diamine component used in the production of polyamides by polycondensing a diamine component and a dicarboxylic acid component. It also describes that a polyamide using equimolar bis-aminomethyl-norbornene and 2-methylpentamethylene as the diamine components is transparent and has a high solidification point. Furthermore, it describes that in order to increase the transparency of the polyamide, crystallization does not occur at all during cooling by selecting the diamine component.

[0005] Patent Document 3 describes that, as a diamine component, a portion of hexamethylene diamine is a mixture of equivalent amounts of 2,5-bis-aminomethyl-norbornene and 2,6-bis-aminomethyl-norbornene, and the molar ratio of said mixture is 20 mol% or less. It describes that, by doing so, a transparent polyamide having a high transition temperature is obtained.

[0006] Patent Document 4 describes that the mixing ratio of bis-aminomethyl-norbornene as a diamine component is 17% by weight or more. Specifically, it describes that a polyamide obtained by mixing hexamethylene diamine and bis-aminomethyl-norbornene, such that the weight ratio of hexamethylene diamine / bis-aminomethyl-norbornene is 30 / 70 (molar ratio is 36 / 64), has a high glass transition point. Prior art literature

[0007] Japanese Patent Publication No. Hei 06-032979, Japanese Patent Publication No. Sho 48-60193, Japanese Patent Publication No. Sho 53-125497, Japanese Patent Publication No. Sho 63-154739 The problem to be solved

[0008] As described in Patent Document 1, it is known that the heat aging resistance of a polyamide resin composition can be improved by a copper-based heat stabilizer. However, according to the inventors' new findings, there is a problem in that the original tensile strength of the polyamide resin composition is reduced by the addition of a copper-based heat stabilizer. The problem caused by the reduction in tensile strength is particularly pronounced when a molded article of the polyamide resin composition is used in a high-temperature environment. Furthermore, in recent years, there has been an increasing demand for further improving the long-term heat resistance of polyamide resin compositions, and there is a need for the development of a polyamide resin composition that can maintain a predetermined tensile strength for a longer period of time in a high-temperature environment.

[0009] In light of these circumstances, the present disclosure aims to provide a polyamide resin composition capable of suppressing the decrease in tensile strength caused by the addition of a copper-based heat stabilizer at high temperatures and maintaining a predetermined tensile strength for a longer period of time under high-temperature environments, and a polyamide molded article comprising said polyamide resin composition. means of solving the problem

[0010] [1] A polyamide resin composition comprising a polyamide resin and a copper-based heat stabilizer, wherein the copper content of the copper-based heat stabilizer is 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin, and the polyamide resin comprises a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine, wherein the component unit (a) derived from the dicarboxylic acid comprises a component unit derived from an aromatic dicarboxylic acid or a dicyclic dicarboxylic acid, and the component unit (b) derived from the diamine comprises a component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms, which is greater than 50 mol% and less than 90 mol% with respect to the total moles of the component unit (b) derived from the diamine, and a component unit (b1) derived from an alkylene diamine having 10 mol% or more and less than 50 mol% with respect to the total moles of the component unit (b) derived from the diamine, A polyamide resin composition comprising a component unit (b2) derived from a diamine represented by formula (1).

[0011]

[0012] (In equation (1),

[0013] m and n are each independently 0 or 1, and

[0014] -X- is a single bond, or a divalent group selected from the group consisting of -O-, -S-, -SO2-, -CO-, and -CH2-)

[0015] [2] The polyamide resin described in [1] comprises a component unit (b2) derived from diamine represented by the formula (1), which is 15 mol% or more and less than 45 mol% of the total moles of the component unit (b) derived from diamine.

[0016] [3] The component unit (b1) derived from an alkylene diamine with 4 to 18 carbon atoms is a polyamide resin composition described in [1] or [2], comprising a component unit derived from a straight-chain alkylene diamine or a branched-chain alkylene diamine.

[0017] [4] The polyamide resin composition described in [3], wherein the straight-chain alkylene diamine or branched-chain alkylene diamine is a diamine selected from the group consisting of 1,4-diaminobutane, 1,6-diaminohexane, 1,9-noneneindiamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine.

[0018] [5] The above-mentioned aromatic dicarboxylic acid or cyclocyclic dicarboxylic acid is terephthalic acid, naphthalene dicarboxylic acid, or cyclohexane dicarboxylic acid, a polyamide resin composition described in any one of [1] to [4].

[0019] [6] A polyamide resin composition described in any one of [1] to [5], wherein the melting point (Tm) of the polyamide resin is 280°C or higher.

[0020] [7] The above polyamide resin is a crystalline polyamide resin, a polyamide resin composition described in any one of [1] to [6].

[0021] [8] A polyamide resin composition described in any one of [1] to [7], wherein the melting heat (ΔH) of the polyamide resin is 10 mJ / mg or more.

[0022] [9] A polyamide resin composition described in any one of [1] to [8], which is a resin composition for automotive parts.

[0023]

[10] A polyamide molded body comprising a polyamide resin composition described in any one of [1] to [9].

[0024]

[11] A polyamide molded body as described in

[10] , which is a component of the vehicle. Effects of the invention

[0025] According to the present disclosure, a polyamide resin composition that can suppress the decrease in tensile strength caused by the addition of a copper-based heat stabilizer and can also maintain a predetermined tensile strength for a longer period of time under a high-temperature environment, and a polyamide molded article comprising said polyamide resin composition can be provided. Specific details for implementing the invention

[0026] 1. Polyamide resin composition

[0027] The polyamide resin composition of the present disclosure is a resin composition in which the main component of the resin component is a polyamide resin. The term "main component" means that the proportion of the polyamide resin in the resin component is 50 mass% or more. The proportion of the polyamide resin in the resin component is preferably 60 mass% or more, more preferably 70 mass% or more, more preferably 80 mass% or more, and particularly preferably 90 mass% or more. The upper limit of the proportion of the polyamide resin in the resin component is not particularly limited, but it may be 100 mass% or less, 90 mass% or less, or 80 mass% or less.

[0028] It is preferable that the proportion of polyamide resin included in the polyamide resin composition be 20 mass% or more and 80 mass% or less with respect to the total mass of the polyamide resin composition.

[0029] 1-1. Polyamide Resin

[0030] The polyamide resin may be a polyamide resin comprising a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine. In order to appropriately increase the melting point (Tm) and glass transition temperature (Tg) of the polyamide resin, it is preferable that the component unit (a) derived from the dicarboxylic acid comprises a component unit derived from an aromatic dicarboxylic acid or a dicyclic dicarboxylic acid, and the component unit (b) derived from the diamine comprises a component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms, which is greater than 50 mol% and less than 90 mol% with respect to the total moles of the component unit (b) derived from the diamine, and a component unit (b2) derived from the diamine represented by the following formula (1), which is 10 mol% or more and less than 50 mol% with respect to the total moles of the component unit (b) derived from the diamine.

[0031]

[0032] (In equation (1),

[0033] m and n are each independently 0 or 1, and

[0034] -X- is a single bond, or a divalent group selected from the group consisting of -O-, -S-, -SO2-, -CO-, and -CH2-)

[0035] [Component unit derived from dicarboxylic acid (a)]

[0036] If a polyamide resin includes a component unit (a) derived from a dicarboxylic acid, which is derived from an aromatic dicarboxylic acid or a dicarboxylic acid, the melting point (Tm) and crystallinity can be sufficiently increased.

[0037] Examples of aromatic dicarboxylic acids include terephthalic acid, naphthalene dicarboxylic acid, and their esters. Examples of alicyclic dicarboxylic acids include cyclohexane dicarboxylic acid and its esters.

[0038] In the present disclosure, the component unit (a) derived from a dicarboxylic acid preferably comprises a component unit (a1) derived from terephthalic acid, naphthalene dicarboxylic acid, or cyclohexane dicarboxylic acid. These component units (a1) can increase the crystallinity of the polyamide, for example, unlike isophthalic acid. The content of these component units (a1) is greater than 20 mol% and less than or equal to 100 mol% with respect to the total molar amount of component units (a) derived from dicarboxylic acid, in order to secure the crystallinity of the polyamide resin. With respect to further increasing the crystallinity of the polyamide resin, the content of these component units (a1) is preferably 45 mol% or more with respect to the total molar amount of component units (a) derived from dicarboxylic acid, more preferably 50 mol% or more, more preferably greater than 80 mol%, and particularly preferably greater than 90 mol%. The upper limit of the content of the component unit (a1) may be 100 mol% or 99 mol% or less with respect to the total moles of the component unit (a) derived from the dicarboxylic acid. Among these, from the perspective of obtaining a polyamide resin with high crystallinity and high heat resistance, it is more preferable that the component unit (a1) be a component unit derived from terephthalic acid.

[0039] The component unit (a) derived from a dicarboxylic acid may additionally include, to the extent that it does not impair the effects of the present disclosure, a component unit (a2) derived from an aromatic dicarboxylic acid other than the component unit (a1), a component unit (a3) ​​derived from an aliphatic dicarboxylic acid having 4 to 18 carbon atoms, or a component unit (a4) derived from a polycarboxylic acid of 3 basic or higher.

[0040] Examples of component units (a2) derived from aromatic dicarboxylic acids other than terephthalic acid include component units derived from isophthalic acid and 2-methylterephthalic acid, and preferably component units derived from isophthalic acid. In order to facilitate securing the crystallinity of the polyamide resin, the content of these component units (a2) is preferably 1 mol% or more and 50 mol% or less with respect to the total molar amount of component units (a) derived from dicarboxylic acids, more preferably 1 mol% or more and 20 mol% or less, more preferably 1 mol% or more and 10 mol% or less, and particularly preferably 1 mol% or more and 5 mol% or less.

[0041] The component unit (a3) ​​derived from an aliphatic dicarboxylic acid having 4 to 18 carbon atoms is a component unit derived from an aliphatic dicarboxylic acid having 4 to 18 alkylene groups, and is preferably a component unit derived from an aliphatic dicarboxylic acid having 6 to 12 alkylene groups. Examples of aliphatic dicarboxylic acids include component units derived from malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, and souveric acid, and preferably is a component unit derived from adipic acid and sebacic acid. The content of these component units (a3) ​​is preferably 0 mol% or more and 40 mol% or less with respect to the total moles of component units (a) derived from dicarboxylic acid, with respect to securing the crystallinity of the polyamide resin, more preferably 0 mol% or more and 20 mol% or less, more preferably 1 mol% or more and 10 mol% or less, and particularly preferably 1 mol% or more and 5 mol% or less.

[0042] Examples of component units (a4) derived from polycarboxylic acids of tribasicity or higher include component units derived from trimellitic acid, pyromellitic acid, and esters thereof. The content of such component units derived from polycarboxylic acids can be 0 mol% or more and 5 mol% or less with respect to the total number of component units (a) derived from component units derived from dicarboxylic acids.

[0043] However, from the perspective of making it difficult to impair the crystallinity of the resin, the content of component units derived from isophthalic acid or component units derived from aliphatic dicarboxylic acids having 4 to 18 carbon atoms other than adipic acid is low, specifically 20 mol% or less with respect to the total moles of component units (a) derived from dicarboxylic acids, and more preferably 10 mol% or less.

[0044] [Component unit derived from diamine (b)]

[0045] If a polyamide resin includes a component unit (b) derived from a diamine, in addition to a component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms, a component unit (b2) derived from an alkylene diamine having a specific cyclic structure (a diamine represented by formula (1)), the glass transition temperature (Tg) can be sufficiently increased.

[0046] That is, the component unit (b2) derived from diamine represented by formula (1) has a non-linear structure, which reduces the mobility of the molecular chains of the polyamide resin. Therefore, the component unit (b2) derived from diamine represented by formula (1) can make the glass transition temperature (Tg) of the polyamide resin having said component unit (b2) higher than that of the polyamide resin not having said component unit (b2). As a result, it is thought that the polyamide resin having said component unit (b2) has high mechanical strength even in the high-temperature range and can maintain this high mechanical strength for a long time.

[0047] Furthermore, the component unit (b2) derived from the diamine represented by formula (1) can appropriately lower the melting point (Tm) of the polyamide resin having said component unit (b2) compared to the polyamide resin not having said component unit (b2). By this, the polyamide resin having said component unit (b2) has high fluidity during injection molding and also high moldability.

[0048] However, according to the findings of the inventors, the copper-based heat stabilizer described below is difficult to decompose at high temperatures, thereby increasing the heat aging resistance of the polyamide resin composition; however, since it is a foreign substance within the resin composition and is a compound containing a metal with properties significantly different from those of the resin, it significantly reduces the crystallinity of the polyamide resin, making it easy to lower the original tensile strength of the polyamide resin composition from the initial manufacturing stage. Furthermore, in high-temperature environments where the fluidity of the resin is high, the copper-based heat stabilizer, which is a foreign substance, is more likely to move more freely within the composition, and since the elongation, shrinkage, or crystallization of the resin molecules is more likely to be inhibited by such movement, the decrease in tensile strength is more likely to appear more significantly. On the other hand, the component unit (b2) derived from diamine represented by formula (1) restricts the movement of the copper-based heat stabilizer in high-temperature environments by increasing the glass transition temperature of the polyamide resin. As a result, it is believed that inhibition of elongation, shrinkage, or crystallization of resin molecules by copper-based heat stabilizers is less likely to occur, thereby suppressing the decrease in tensile strength of the polyamide resin composition under high-temperature environments.

[0049] In addition, the component unit (b2) derived from diamine represented by formula (1) has a cyclic structure, so it is difficult for the molecular chains of the resin to break even when left in a high-temperature environment for a long time, thereby increasing the long-term heat resistance of the polyamide resin itself. Therefore, it is thought that the component unit (b2) derived from diamine represented by formula (1) makes it easier to maintain the tensile strength of the molded body of the polyamide resin composition for a longer period of time, even in a high-temperature environment.

[0050] In addition, since the polyamide resin has crystallinity based on component units (b1) derived from alkylene diamines with 4 to 18 carbon atoms, it has high fluidity and mechanical strength during injection molding (of the polyamide resin itself). Furthermore, it is thought that the polyamide resin has high mechanical strength even in the high temperature range because it has a high glass transition temperature (Tg), and it is easy to maintain these high mechanical strengths.

[0051] The number of carbon atoms of the alkylene diamine, which is the raw material of the component unit (b1), is 4 to 18 or fewer, is more preferably 4 to 10 or fewer from the perspective of making it difficult to lower the Tg of the resin.

[0052] Alkylene diamines having 4 to 18 carbon atoms may include straight-chain alkylene diamines or branched-chain alkylene diamines. From the perspective of increasing the crystallinity of the resin, it is preferable that alkylene diamines having 4 to 18 carbon atoms include straight-chain alkylene diamines. That is, it is preferable that component units derived from alkylene diamines having 4 to 18 carbon atoms include component units derived from straight-chain alkylene diamines.

[0053] Examples of alkylene diamines having 4 to 18 carbon atoms include straight-chain alkylene diamines such as 1,4-diaminobutane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine, and branched-chain alkylene diamines such as 2-methyl-1,5-pentanediamine and 2-methyl-1,8-octanediamine. Among these, 1,4-diaminobutane, 1,6-diaminohexane, 1,9-noneneindiamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine are preferred, and 1,6-diaminohexane and 1,10-decanediamine are preferred. These alkylene diamines may be one type or two or more types.

[0054] It is preferable that the content of component units (b1) derived from alkylene diamines having 4 to 18 carbon atoms be greater than 50 mol% and less than 90 mol% with respect to the total molar amount of component units (b) derived from diamines. If the above content is greater than 50 mol%, the crystallinity of the polyamide resin can be sufficiently increased, thereby further increasing the fluidity and mechanical strength of the polyamide resin itself during injection molding. If the above content is less than 90 mol%, the content of component units (b2) derived from diamines represented by formula (1) can be increased. By doing so, the glass transition temperature (Tg) of the polyamide resin can be increased to increase mechanical strength in the high-temperature range, and the (Tm) of the polyamide resin can be appropriately lowered to increase moldability.

[0055] In the same regard, the content of component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms is more preferably 55 mol% to 85 mol% with respect to the total moles of component unit (b) derived from diamine, and more preferably 60 mol% to 80 mol%.

[0056] On the other hand, it is preferable that the content of the component unit (b2) derived from diamine represented by formula (1) be 10 mol% or more and less than 50 mol% with respect to the total moles of the component unit (b) derived from diamine. If the above content is 10 mol% or more, the glass transition temperature (Tg) of the polyamide resin can be increased to increase mechanical strength in the high-temperature range, and the (Tm) of the polyamide resin can be appropriately lowered to increase moldability. If the above content is less than 50 mol%, the content of the component unit (b1) derived from alkylene diamine with 4 to 18 carbon atoms can be increased. By doing so, in addition to sufficiently increasing the crystallinity of the polyamide resin to further increase the mechanical strength of the molded body, the decrease in fluidity of the polyamide resin itself caused by the component unit (b2) derived from diamine represented by formula (1) can be suppressed.

[0057] In the same regard, the content of the component unit (b2) derived from diamine represented by formula (1) is more preferably 15 mol% or more and less than 45 mol% with respect to the total moles of the component unit (b) derived from diamine, more preferably 20 mol% or more and 40 mol% or less, more preferably 20 mol% or more and 38 mol% or less, and particularly preferably 22 mol% or more and 35 mol% or less.

[0058] Furthermore, according to the findings of the inventors, when glass fibers treated with a carboxyl group-containing water-retaining agent are added to a polyamide resin composition, the fluidity of the polyamide resin composition may decrease. The above decrease in fluidity was also observed when glass fibers treated with a water-retaining agent or surface treatment agent having other acidic groups were added to the polyamide resin composition. The decrease in fluidity when glass fibers treated with an acidic group-containing water-retaining agent or surface treatment agent are added to the polyamide resin composition is thought to be caused by the acidic group of the water-retaining agent or surface treatment agent reacting with the amino end of the polyamide resin during the melting of the polyamide resin composition. That is, the above reaction causes the polyamide resin and the glass fiber to bond together via the water-retaining agent or surface treatment agent, thereby increasing the apparent molecular weight of the polyamide resin. And, it is thought that the fluidity of the polyamide resin composition decreases due to the increase in the apparent molecular weight. In contrast, the component unit (b2) derived from the diamine represented by formula (1) can bend the molecular chain of the polyamide resin to create appropriate steric hindrance, thereby further inhibiting the reaction between the acidic group of the water-conducting agent or surface treatment agent and the amino terminus of the polyamide resin. It is believed that this suppresses the increase in the apparent molecular weight of the polyamide resin, thereby obtaining an additional effect of suppressing the decrease in fluidity of the polyamide resin composition when using a water-conducting agent or surface treatment agent having an acidic group.

[0059] The component unit (b) derived from diamine may additionally include a component unit (b3) derived from another diamine, to the extent that it does not impair the effects of the present disclosure. Examples of other diamines include aromatic diamines or alicyclic diamines. The content of the component unit (b3) derived from another diamine may be 50 mol% or less with respect to the total moles of the component unit (b) derived from diamine.

[0060] In order to increase thermal stability during compounding or molding, or to further increase mechanical strength, at least some of the end groups of the polyamide resin may be encapsulated by a end encapsulator. For example, when the end of the molecule is a carboxyl group, it is preferable that the end encapsulator be a monoamine, and when the end of the molecule is an amino group, it is preferable that the end encapsulator be a monocarboxylic acid.

[0061] Examples of monoamines include aliphatic monoamines including methylamine, ethylamine, propylamine, and butylamine, etc., alicyclic monoamines including cyclohexylamine and dicyclohexylamine, etc., and aromatic monoamines including aniline and toluidine, etc. Examples of monocarboxylic acids include aliphatic monocarboxylic acids having 2 to 30 carbon atoms including acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, oleic acid, and linoleic acid, etc., aromatic monocarboxylic acids including benzoic acid, toluic acid, naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid, etc., and alicyclic monocarboxylic acids including cyclohexanecarboxylic acid, etc. Aromatic monocarboxylic acids and alicyclic monocarboxylic acids may have substituents in the cyclic portion.

[0062] [Physical properties]

[0063] The polyamide resin can have a melting point (Tm) measured by differential scanning calorimetry (DSC) of 280°C or higher and 330°C or lower, and a glass transition temperature (Tg) measured by DSC of 135°C or higher and 180°C or lower.

[0064] If the melting point (Tm) of the polyamide resin is 280°C or higher, the mechanical strength or heat resistance of the polyamide resin composition or the molded article in the high-temperature range is less likely to be damaged, and if it is 330°C or lower, there is no need to raise the molding temperature excessively, so the molding processability of the polyamide resin composition is more likely to be good. From the above perspective, it is more preferable that the melting point (Tm) of the polyamide resin be 290°C or higher and 330°C or lower, and more preferable that it be 300°C or higher and 330°C or lower.

[0065] If the glass transition temperature (Tg) of the polyamide resin is 135°C or higher, the heat resistance of the polyamide resin composition or the molded article is less likely to be damaged, and at the same time, the mechanical strength in the high-temperature range can be increased. If the glass transition temperature (Tg) of the polyamide resin is 180°C or lower, the moldability of the polyamide resin composition is more likely to be good. From the above perspective, it is more preferable that the glass transition temperature (Tg) of the polyamide resin be 140°C or higher and 170°C or lower.

[0066] It is preferable that the melting heat (ΔH) of the polyamide resin be 10 mJ / mg or higher. If the melting heat (ΔH) of the polyamide resin is 10 mJ / mg or higher, it is easy to increase fluidity or mechanical strength during injection molding because it has crystallinity. From the same perspective, it is more preferable that the melting heat (ΔH) of the polyamide resin be 15 mJ / mg or higher, and more preferable that it be 20 mJ / mg or higher. Meanwhile, the upper limit of the melting heat (ΔH) of the polyamide resin is not particularly limited, but from the perspective of not impairing moldability, it may be 90 mJ / mg.

[0067] Meanwhile, the heat of fusion (ΔH), melting point (Tm), and glass transition temperature (Tg) of the polyamide resin can be measured using a differential scanning calorimeter (DSC220C type, manufactured by Seiko Instruments).

[0068] Specifically, about 5 mg of polyamide resin is sealed in a measuring aluminum pan and heated from room temperature to 350°C at a rate of 10°C / min. To completely melt the resin, it is maintained at 350°C for 3 minutes, and then cooled to 30°C at a rate of 10°C / min. After being held at 30°C for 5 minutes, a second heating is performed to 350°C at a rate of 10°C / min. The temperature (°C) of the endothermic peak during this second heating is set as the melting point (Tm) of the polyamide resin, and the displacement point corresponding to the glass transition is set as the glass transition temperature (Tg). The heat of fusion (ΔH) is calculated from the area of ​​the endothermic peak during the second heating process in accordance with JIS K7122.

[0069] The melting point (Tm), glass transition temperature (Tg), and heat of fusion (ΔH) of the polyamide resin can be adjusted by the structure of the component unit (a) derived from the dicarboxylic acid, the content of the component unit (b2) derived from the diamine represented by formula (1), the ratio of the component unit (b1) derived from the alkylene diamine with 4 to 18 carbon atoms and the component unit (b2) derived from the diamine represented by formula (1), and the number of carbon atoms of the alkylene diamine with 4 to 18 carbon atoms.

[0070] In addition, when the heat of fusion (ΔH) of the polyamide resin is increased, it is desirable to keep the content or content ratio (the ratio of the component unit (b2) to the total moles of the component unit (b) derived from diamine) low. On the other hand, when the glass transition temperature (Tg) of the polyamide resin is increased and the melting point (Tm) is decreased, for example, it is desirable to keep the content or content ratio (the ratio of the component unit (b2) to the total moles of the component unit (b) derived from diamine) high.

[0071] The intrinsic viscosity [η] of the polyamide resin, measured in 96.5% sulfuric acid at a temperature of 25°C, is preferably 0.6 dl / g or higher and 1.5 dl / g or lower. If the intrinsic viscosity [η] of the polyamide resin is 0.6 dl / g or higher, it is easy to sufficiently increase the mechanical strength (toughness, etc.) of the molded article, and if it is 1.5 dl / g or lower, it is difficult to impair the fluidity of the polyamide resin composition during molding. From the same perspective, it is more preferable that the intrinsic viscosity [η] of the polyamide resin is 0.8 dl / g or higher and 1.2 dl / g or lower. The intrinsic viscosity [η] can be adjusted by the amount of end encapsulation of the polyamide resin, etc.

[0072] The ultimate viscosity of polyamide resin can be measured in accordance with JIS K6810-1977.

[0073] Specifically, 0.5 g of polyamide resin is dissolved in 50 ml of 96.5% sulfuric acid solution to form a sample solution. The flow rate of this sample solution can be measured using a Ubélode viscometer under conditions of 25 ± 0.05°C, and the obtained value can be calculated by applying it to the following formula.

[0074] [η]=ηSP / [C(1+0.205ηSP)]

[0075] In the above equation, each algebra or variable represents the following.

[0076] [η]: Limiting viscosity (dl / g)

[0077] ηSP: Specific viscosity

[0078] C: Sample concentration (g / dl)

[0079] ηSP is calculated by the following formula.

[0080] ηSP=(t-t0) / t0

[0081] t: Flow time of sample solution (seconds)

[0082] t0: Blank sulfuric acid flow rate (seconds)

[0083] [Manufacturing Method]

[0084] Polyamide resins can be prepared, for example, by polycondensing the aforementioned dicarboxylic acid and the aforementioned diamine in a homogeneous solution. Specifically, they can be prepared by obtaining a lower-order condensate by heating the dicarboxylic acid and the diamine in the presence of a catalyst as described in International Publication No. 03 / 085029, and then polycondensing the molten lower-order condensate by applying shear stress to it.

[0085] From the perspective of adjusting the intrinsic viscosity of the polyamide resin, the aforementioned terminal encapsulant may be added to the reaction system. The intrinsic viscosity [η] (or molecular weight) of the polyamide resin can be adjusted by the amount of terminal encapsulant added.

[0086] A terminal encapsulant is added to a reaction system of a dicarboxylic acid and a diamine. The amount added is preferably 0.07 moles or less per 1 mole of the total amount of dicarboxylic acid, and more preferably 0.05 moles or less.

[0087] 1-2. Heat Stabilizer

[0088] Copper-based heat stabilizers can improve the fluidity of the polyamide resin composition during molding. In addition, copper-based heat stabilizers improve the heat aging resistance of the polyamide resin composition.

[0089] Copper-based heat stabilizers include (i) a salt of a halogen and a metal element of Group 1 or Group 2 of the periodic table (halogen metal salt), (ii) a copper compound, and, if necessary, may additionally include (iii) a metal salt of a higher fatty acid.

[0090] (i) Examples of halogen metal salts include potassium iodide, potassium bromide, potassium chloride, sodium iodide, and sodium chloride. Among these, potassium iodide and potassium bromide are preferred. The halogen metal salts may include only one type or two or more types.

[0091] (ii) Examples of copper compounds include copper halides, copper salts (sulfates, acetates, propionates, benzosates, adiposes, terephthalates, salicylates, nicotinates, and stearates, etc.), and copper chelate compounds (compounds of copper and ethylenediamine or ethylenediamine tetraacetic acid, etc.). Among these, copper iodide, cuprous bromide, cupric bromide, cuprous chloride, and copper acetate are preferred. Copper compounds may be included in only one type or in two or more types.

[0092] (i) The mass ratio of the halogen metal salt and (ii) the copper compound can be adjusted so that the molar ratio of the halogen to the copper is 0.1 / 1 to 200 / 1, preferably 0.5 / 1 to 100 / 1, more preferably 2 / 1 to 40 / 1, in order to facilitate improving the heat resistance or corrosion resistance of the molded body during manufacturing.

[0093] (iii) Examples of metal salts of higher fatty acids include metal salts of higher saturated fatty acids and metal salts of higher unsaturated fatty acids.

[0094] The higher saturated fatty acid metal salt is preferably a metal salt of a saturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as a metal element of Group 1, 2, or 3 of the periodic table, zinc, and aluminum. Such a higher saturated fatty acid metal salt is represented by the following formula (2).

[0095] CH3(CH2) n COO(M1) . . . (2)

[0096] (In Equation (2), the metal element (M1) is an element of Group 1, 2, or 3 of the periodic table, zinc, or aluminum, and n can be 8 to 30.)

[0097] Examples of metal salts of higher saturated fatty acids include lithium, sodium, magnesium, calcium, zinc, and aluminum salts of capric acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanic acid, arachnic acid, behenic acid, lignoceric acid, cerotic acid, heptacosonic acid, montanic acid, melisic acid, and racerosic acid.

[0098] The metal salt of the higher unsaturated fatty acid is preferably a metal salt of an unsaturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as an element of groups 1, 2, or 3 of the periodic table, zinc, and aluminum.

[0099] Examples of metal salts of higher unsaturated fatty acids include lithium, sodium, magnesium, calcium, zinc, and aluminum salts of undecylenic acid, oleic acid, elaidic acid, cetolic acid, erucic acid, brasidic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, stearic acid, 2-hexadecenoic acid, 7-hexadecenoic acid, 9-hexadecenoic acid, gadoleic acid, gadoelaidic acid, and 11-eicocenic acid.

[0100] Examples of copper-based heat stabilizers include a mixture of 10 mass% copper iodide (I) and 90 mass% potassium iodide, or a mixture of 14.3 mass% copper iodide (I) and 85.7 mass% potassium iodide / calcium distearate (98:2 mass ratio).

[0101] The copper content included in the copper-based heat stabilizer in the polyamide resin composition is preferably 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin, and preferably 0.002 parts by mass or more and 0.030 parts by mass or less, more preferably 0.003 parts by mass or more and 0.020 parts by mass or less, and even more preferably 0.005 parts by mass or more and 0.010 parts by mass or less. If the amount of copper included in the copper-based heat stabilizer is 0.001 parts by mass or more per 100 parts by mass of the polyamide resin, the fluidity and heat aging resistance of the resin composition can be further improved, and if it is 0.050 parts by mass or less, the mechanical strength of the molded article is less likely to be damaged.

[0102] The content of the copper-based heat stabilizer in the polyamide resin composition is set such that the content of copper derived from said copper-based heat stabilizer falls within the above range. For example, the content of the copper-based heat stabilizer in the polyamide resin composition may be 0.01 mass% or more and 3 mass% or less, preferably 0.1 mass% or more and 3 mass% or less, with respect to the total mass of said resin composition, and more preferably 0.1 mass% or more and 0.5 mass%. If the amount of the copper-based heat stabilizer is 0.01 mass% or more with respect to the total mass of the resin composition, the fluidity and heat aging resistance of the resin composition can be further enhanced, and if it is 3 mass% or less, the mechanical strength of the molded article is less likely to be damaged.

[0103] 1-3. Other ingredients

[0104] The polyamide resin composition may include other known components.

[0105] Examples of other components include reinforcing agents, crystallization nucleating agents, lubricants, flame retardants, corrosion resistance enhancers, anti-drip agents, ion capture agents, elastomers (rubber), antistatic agents, release agents, antioxidants (phenols, amines, sulfurs, and sulfates, etc.), heat stabilizers (lactone compounds, vitamin E compounds, hydroquinones, copper halides and iodine compounds, etc.), light stabilizers (benzotriazoles, triazines, benzophenones, benzoates, hindered amines and oxanilides, etc.), and other polymers (polyolefins, olefin copolymers such as ethylene-propylene copolymer, ethylene-1-butene copolymer, olefin copolymers such as propylene-1-butene copolymer, polystyrene, polyamide, polycarbonate, polyacetal, polysulfone, polyphenylene oxide, fluoropolymer, silicone resin, and LCP). Among these, it is desirable for the polyamide resin composition to additionally include a reinforcing material from the perspective of increasing the mechanical strength of the molded article.

[0106] Reinforcing materials can impart high mechanical strength to a polyamide resin composition. Examples of reinforcing materials include fibrous reinforcing materials such as glass fiber, wollastonite, potassium titanate whiskers, calcium carbonate whiskers, aluminum borate whiskers, magnesium sulfate whiskers, zinc oxide whiskers, milled fiber, and cut fiber, as well as granular reinforcing materials. Among these, one type may be used alone, or two or more types may be used in combination. Among these, wollastonite, glass fiber, and potassium titanate whiskers are preferred due to factors such as ease of increasing the mechanical strength of the molded article, wollastonite or glass fiber are more preferred, and glass fiber is even more preferred.

[0107] The type of glass fiber is not particularly limited as long as it is used for reinforcing the resin, and it may be chopped strands or milled fibers with shorter fiber lengths. In addition, the cross-sectional shape of the glass fiber may be circular, or non-circular, such as elliptical or oblong.

[0108] The average fiber length of the glass fiber can be, for example, 1 μm or more and 20 mm or less, preferably 5 μm or more and 10 mm or less, from the perspective of increasing the moldability of the resin composition and increasing the mechanical strength or heat resistance of the obtained molded article. In addition, the aspect ratio of the glass fiber can be, for example, 5 or more and 2000 or less, preferably 30 or more and 600 or less.

[0109] The average fiber length and average fiber diameter of glass fibers can be measured by the following method.

[0110] 1) Dissolve the resin composition in a hexafluoroisopropanol / chloroform solution (0.1 / 0.9 volume%), then filter to obtain a filtrate.

[0111] 2) The filtrate obtained in 1) above is dispersed in water, and the fiber length (Li) and fiber diameter (di) of each of 300 arbitrary fibers are measured using an optical microscope (magnification: 50x). Let qi be the number of fibers with a fiber length of Li, and calculate the weight-average length (Lw) based on the following formula, and use this as the average fiber length of the glass fiber.

[0112] Weight-average length (Lw) = (Σqi × Li 2 ) / (Σqi×Li)

[0113] Likewise, let ri be the number of fibers with a fiber diameter of Di, calculate the weight average diameter (Dw) based on the following formula, and set this as the average fiber diameter of the glass fiber.

[0114] Weight-average diameter (Dw) = (Σri × Di 2 ) / (Σri×Di)

[0115] The content of glass fiber is not particularly limited, but can be, for example, 15 mass% or more and 70 mass% or less with respect to the total mass of the polyamide resin composition, preferably 15 mass% or more and 50 mass% or less, and more preferably 20 mass% or more and 50 mass% or less.

[0116] The content of glass fiber is not particularly limited, but can be 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of polyamide resin, preferably 0.002 parts by mass or more and 0.040 parts by mass or less, and more preferably 0.005 parts by mass or more and 0.030 parts by mass or less.

[0117] Glass fibers include a surface treatment agent or a water treatment agent.

[0118] The surface treatment agent or the water treatment agent may be any known surface treatment agent or water treatment agent used for glass fibers incorporated into a polyamide resin composition. However, the surface treatment agent or the water treatment agent has an acidic group. Examples of acidic groups include a carboxyl group, an acid anhydride group, an ester group, and a sulfonic acid group. Among these, a carboxyl group, an acid anhydride group, and an ester group are preferred, and a carboxyl group and an acid anhydride group are more preferred. The ester group may be a functional group derived from a carboxylic acid ester.

[0119] Examples of surface treatment agents having acidic groups include silane coupling agents containing acid anhydride groups such as 3-trimethoxysilylpropylsuccinic acid anhydride.

[0120] Examples of water treatment agents having an acidic group include a homopolymer or copolymer of an unsaturated carboxylic acid, or a water treatment agent comprising a copolymer of an unsaturated carboxylic acid or its anhydride and an unsaturated monomer.

[0121] Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, cinnamic acid, itaconic acid, fumaric acid, mesaconic acid, citraconic acid, and maleic acid. Examples of anhydrous unsaturated carboxylic acids include maleic anhydride, itaconic anhydride, and dodeceneylsuccinic anhydride. Among these, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred.

[0122] Examples of unsaturated monomers include styrene, butadiene, acrylonitrile, vinyl acetate, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, methyl styrene, ethylene, propylene, butylene, isobutylene, and vinyl ether. Among these, methyl acrylate and methyl methacrylate are preferred, and it is more preferable to include both methyl acrylate and methyl methacrylate.

[0123] When the growth agent comprises a copolymer of the unsaturated carboxylic acid or its anhydride and an unsaturated monomer, it is preferable that the ratio of the unsaturated carboxylic acid or its anhydride to the total mass of the copolymer be 20 mass% or more and 60 mass% or less. If the ratio is 20 mass% or more, the effect of improving the mechanical strength of the polyamide resin composition is significant by increasing the chemical interaction with the polyamide resin by the acidic group (carboxyl group). If the ratio is 60 mass% or less, the effect of improving the mechanical strength of the polyamide resin composition is significant by increasing the molecular weight (chain length) of the copolymer and increasing the physical interaction with the polyamide resin.

[0124] The above homopolymer or copolymer may be used in combination with other resins, such as uretane resin and epoxy resin.

[0125] Glass fibers containing a surface treatment agent or a water treatment agent can be obtained, for example, by applying (applying) the surface treatment agent or water treatment agent to a fiber strand using a known method such as a roller-type applicator during the manufacturing process of glass fibers, and drying to react.

[0126] The amount of surface treatment agent or water-container applied is preferably 0.2 parts by mass or more and 3 parts by mass or less in terms of solid fraction with respect to 100 parts by mass of glass fiber, more preferably 0.2 parts by mass or more and 2 parts by mass or less, and even more preferably 0.3 parts by mass or more and 2 parts by mass or less. If the amount of application is 0.2 parts by mass or more, the cohesiveness of the glass fiber is further improved. In addition, if the amount of application is 2 parts by mass or less, the thermal stability of the resin composition is further improved.

[0127] The content of reinforcing materials such as glass fibers is not particularly limited, but can be, for example, 15 mass% or more and 70 mass% or less with respect to the total mass of the polyamide resin composition.

[0128] Nucleating agents can increase the degree of crystallization of a molded body. Examples of nucleating agents include metal salt compounds including 2,2-methylenebis(4,6-di-t-butylphenyl)sodium phosphate, tris(pt-butylbenzoic acid)aluminum, and stearate, sorbitol compounds including bis(p-methylbenzylidene)sorbitol and bis(4-ethylbenzylidene)sorbitol, and inorganic materials including talc, calcium carbonate, and hydrotalcite. Among these, talc is preferred for further increasing the degree of crystallization of the molded body. These nucleating agents may be used as a single type or in combination of two or more types.

[0129] The content of the nucleating agent is preferably 0.1 parts by mass or more and 5 parts by mass or less with respect to the total mass of the polyamide resin composition, and more preferably 0.1 parts by mass or more and 3 parts by mass or less. If the content of the nucleating agent is within the above range, it is easy to sufficiently increase the degree of crystallization of the molded body, making it easy to obtain sufficient mechanical strength.

[0130] The lubricant increases the injection fluidity of the polyamide resin composition and also improves the appearance of the resulting molded article. The lubricant may be a metal salt of a fatty acid, such as a metal salt of an oxycarboxylic acid and a metal salt of a higher fatty acid.

[0131] The oxycarboxylic acid constituting the oxycarboxylic acid metal salt may be an aliphatic oxycarboxylic acid or an aromatic oxycarboxylic acid. Examples of aliphatic oxycarboxylic acids include aliphatic oxycarboxylic acids with 10 to 30 carbon atoms, such as α-hydroxymyristic acid, α-hydroxypalmitic acid, α-hydroxystearic acid, α-hydroxyeicosanic acid, α-hydroxydocosanic acid, α-hydroxytetraeicosanic acid, α-hydroxyhexaeicosanic acid, α-hydroxyoctaeicosanic acid, α-hydroxycitriaconic acid, β-hydroxymyristic acid, 10-hydroxydecanoic acid, 15-hydroxypentadecanic acid, 16-hydroxyhexadecanoic acid, 12-hydroxystearic acid, and ricinoleic acid. Examples of aromatic oxycarboxylic acids include salicylic acid, m-oxybenzoic acid, p-oxybenzoic acid, gallic acid, mandelic acid, and tropic acid.

[0132] Examples of metals constituting oxycarboxylic acid metal salts include alkali metals such as lithium, and alkaline earth metals such as magnesium, calcium, and barium.

[0133] Among these, the oxycarboxylic acid metal salt is preferably a metal salt of 12-hydroxystearic acid, and magnesium 12-hydroxystearic acid and calcium 12-hydroxystearic acid are more preferred.

[0134] Examples of higher fatty acids that make up the metal salts of higher fatty acids include higher fatty acids with 15 to 30 carbon atoms, such as stearic acid, oleic acid, behenic acid, behenic acid, and montanic acid.

[0135] Examples of metals that make up higher fatty acid metal salts include calcium, magnesium, barium, lithium, aluminum, zinc, sodium, and potassium.

[0136] Among these, the higher fatty acid metal salts are preferably calcium stearate, magnesium stearate, barium stearate, calcium behenate, sodium moncarbonate, and calcium moncarbonate.

[0137] The lubricant content is preferably 0.01 mass% or more and 1.3 mass% or less with respect to the total mass of the polyamide resin composition. If the lubricant content is 0.01 mass% or more, the fluidity during molding tends to increase, and the appearance of the resulting molded product tends to improve. If the lubricant content is 1.3 mass% or less, gas caused by the decomposition of the lubricant is less likely to be generated during molding, and the appearance of the product tends to be good.

[0138] 1-4. Manufacturing Method

[0139] The polyamide resin composition can be prepared by mixing the aforementioned polyamide resin and, if necessary, other components using a known resin mixing method, such as a Henschel mixer, V blender, ribbon blender, or tumble blender, or by further melt-mixing using a uniscrew extruder, multiscrew extruder, kneader, or Banbury mixer after mixing, and then granulating or grinding.

[0140] 2. Uses of Polyamide Resin Compositions

[0141] The polyamide resin composition of the present disclosure is used as various polyamide molded articles by molding using known molding methods such as compression molding, injection molding, and extrusion molding.

[0142] A molded article of the polyamide resin composition of the present disclosure can be used for various applications. Examples of such uses include automotive exterior parts such as radiator grilles, rear spoilers, wheel covers, wheel caps, cowl vent grilles, air outlet louvers, air scoops, hood bulges, sunroofs, sunroof rails, fenders, and back doors; automotive interior engine parts such as cylinder head covers, engine mounts, air intake manifolds, throttle bodies, air intake pipes, radiator tanks, radiator supports, water pumps, water pump inlets, water pump outlets, thermostat housings, cooling fans, fan shrouds, oil pans, oil filter housings, oil filler caps, oil level gauges, oil pumps, timing belts, timing belt covers, and engine covers; fuel caps, fuel filler tubes, automotive fuel tanks, fuel sender modules, fuel cutoff valves, quick connectors, canisters, fuel delivery pipes, and Automotive fuel system parts such as fuel filler necks, automotive drive system parts such as shift levers, housings, and propeller shafts, automotive chassis parts such as stabilizer bars, linkage rods, and engine mount brackets, automotive functional parts such as window regulators, door locks, door handles, outside / door mirror stays, wipers and their parts, accelerator pedals, pedal modules, joints, resin screws, nuts, bushes, seal rings, bearings, bearing retainers, gears, and actuators, automotive electronics parts such as wire harnesses, connectors, relay blocks, sensor housings, fuse parts, encapsulations, ignition coils, and distributor caps, fuel system parts for general-purpose devices such as fuel tanks for general-purpose devices (brush cutters, lawn mowers, and chainsaws), electrical and electronic parts such as connectors and LED reflectors, construction materials, industrial equipment parts, and, various light bodies or exterior parts such as small light bodies (including light bodies for personal computers or mobile phones), and exterior molded products.

[0143] Among these, the polyamide resin composition of the present disclosure is suitable for use in high-temperature and high-humidity environments, such as in automotive body components, particularly tubes through which antifreeze flows, because the decrease in mechanical strength is minimal even under high-temperature and high-humidity environments. Furthermore, the polyamide resin composition of the present disclosure can be suitably used in automotive electronics components, electrical and electronic components, industrial equipment components, and components of electrical equipment such as bodywork or exterior parts of electrical equipment.

[0144] Examples

[0145] The present disclosure is described below with reference to examples. The scope of the present disclosure is not to be interpreted as limited by the examples.

[0146] Meanwhile, in the following experiments, the melting point (Tm) and glass transition temperature (Tg) of the polyamide resin were measured by the following method.

[0147] (Melting point (Tm), glass transition temperature (Tg), heat of fusion (ΔH))

[0148] The heat of fusion (ΔH), melting point (Tm), and glass transition temperature (Tg) of the polyamide resin were measured using a differential scanning calorimeter (DSC220C type, manufactured by Seiko Instruments).

[0149] Specifically, about 5 mg of polyamide resin was sealed in a measuring aluminum pan and heated from room temperature to 350°C at a rate of 10°C / min. To completely melt the resin, it was held at 350°C for 3 minutes, and then cooled to 30°C at a rate of 10°C / min. After being held at 30°C for 5 minutes, a second heating was performed to 350°C at a rate of 10°C / min. The temperature (°C) of the endothermic peak during this second heating was set as the melting point (Tm) of the polyamide resin, and the displacement point corresponding to the glass transition was set as the glass transition temperature (Tg). The heat of fusion (ΔH) was calculated from the area of ​​the endothermic peak during the second heating process in accordance with JIS K7122.

[0150] (Limited viscosity [η])

[0151] The intrinsic viscosity [η] of the polyamide resin was calculated by dissolving 0.5 g of the polyamide resin in 50 ml of a 96.5% sulfuric acid solution, measuring the flow time of the obtained solution under conditions of 25°C ± 0.05°C using a Uvelohde viscometer, and using the formula: [η] = ηSP / (C(1 + 0.205ηSP)).

[0152] [η]: Limiting viscosity (dl / g)

[0153] ηSP: Specific viscosity

[0154] C: Sample concentration (g / dl)

[0155] t: Flow time of sample solution (seconds)

[0156] t0: Blank sulfuric acid flow rate (seconds)

[0157] ηSP=(t-t0) / t0

[0158] 1. Synthesis / Preparation of Materials

[0159] 1-1. Synthesis of Polyamide Resin

[0160] (Synthesized Example 1)

[0161] 259.5 g (1561.7 mmol) of terephthalic acid, 118.9 g (1023.1 mmol) of 1,6-diaminohexane, 85.0 g (551.1 mmol) of norbornendiamine, 0.37 g of sodium hypophosphite monohydrate, and 81.8 g of distilled water were placed in an autoclave with a net capacity of 1 L and subjected to nitrogen purging. Stirring was initiated at 190°C, and the internal temperature was raised to 250°C over a period of 3 hours. At this time, the internal pressure of the autoclave was increased to 3.0 MPa. After continuing the reaction for 1 hour, the mixture was released into the atmosphere through a spray nozzle installed at the bottom of the autoclave, and the lower condensate was discharged. Subsequently, the lower condensate was cooled to room temperature, then ground using a grinder to a particle size of 1.5 mm or less, and dried at 110°C for 24 hours.

[0162] Next, this lower condensate was placed in a solid-state polymerization apparatus, and after nitrogen substitution, the temperature was raised to 215°C over approximately 1 hour and 30 minutes. After that, the reaction was carried out for 1 hour and 30 minutes, and the temperature was lowered to room temperature.

[0163] Afterwards, the obtained prepolymer was melt-polymerized using a twin-screw extruder with a screw diameter of 30 mm and L / D=36 at a barrel setting temperature of 330℃, a screw rotation speed of 200 rpm, and a resin feed rate of 6 kg / h to obtain polyamide resin 1.

[0164] The intrinsic viscosity [η] of the obtained polyamide resin 1 was 0.97 dl / g, the melting point (Tm) was 312°C, the glass transition temperature (Tg) was 167°C, and the heat of fusion (ΔH) was 44 mJ / mg.

[0165] (Synthesized Example 2)

[0166] Polyamide resin 2 was obtained in the same manner as Synthesis Example 1, except that the amount of 1,6-hexanediamine placed in the autoclave was 280 g (2410 mmol), the amount of terephthalic acid was 277.4 g (1670 mmol), and the amount of isophthalic acid was 119.6 g (720 mmol); 3.66 g (30 mmol) of benzoic acid was added; the amount of sodium hypophosphite monohydrate was 5.7 g; and the amount of distilled water was 545 g.

[0167] The intrinsic viscosity of the obtained polyamide resin 2 was 1.0 dl / g, the melting point (Tm) was 330°C, the glass transition temperature (Tg) was 125°C, and the heat of fusion (ΔH) was 50 J / g.

[0168] 1-2. Heat Stabilizer

[0169] · Copper-based heat stabilizers

[0170] A mixture of 10 mass% copper iodide (I) and 90 mass% potassium iodide was used as a copper-based heat stabilizer.

[0171] · Phenol-based heat stabilizers

[0172] Pentaerythritol tetrakis[3-[3,5-di(tert-butyl)-4-hydroxyphenyl]propionate] (BASF, irganox 1010) was used as a phenolic heat stabilizer.

[0173] · Heat stabilizer of the phosphorus system

[0174] 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspyro[5.5]undecaine (ADEKA, Adeca Starv PEP-36) was used as a phosphorus-based heat stabilizer.

[0175] · Yellow heat stabilizer

[0176] Bis[3-(dodecylthio)propionic acid]2,2-bis[[3-(dodecylthio)-1-oxopropyloxy]methyl]-1,3-propanediyl (Cipro Chemical Co., Ltd., SEENOX412S) was used as a sulfur-based heat stabilizer.

[0177] 1-3. Lubricant

[0178] Sodium moncarbonate (manufactured by Clariant, LICOMONT NAV101; "LICOMONT" is the company's registered trademark)

[0179] 1-4. Nucleating agent

[0180] · Talc (fine particle talc)

[0181] 1-5. Reinforcement

[0182] · Glass fiber containing a carboxyl group-containing growth agent (Owens Corning, FT756D)

[0183] 2. Preparation of a polyamide resin composition

[0184] The above materials were mixed in a tumble blender at the composition ratios shown in Table 1 (units are parts by mass) and melt-kneaded using a 30 mmφ vented twin-screw extruder under cylinder temperature conditions of 300–335°C. Afterward, the mixture was extruded into a strand and cooled in a water bath. Subsequently, the strand was taken out with a pelletizer and cut to obtain a pellet-shaped polyamide resin composition.

[0185] 3. Evaluation

[0186] The obtained polyamide resin composition was evaluated according to the following criteria.

[0187] 3-1. Tensile Strength (at High Temperature)

[0188] Each polyamide resin composition was injection molded under the following conditions to produce ASTM-1 (dumbbell) test specimens with a thickness of 3.2 mm.

[0189] Forming machine: Manufactured by Sumitomo Heavy Industries, Ltd., SE50DU

[0190] Molding machine cylinder temperature: Melting point of polyamide resin + 10℃

[0191] Mold temperature: Glass transition temperature of polyamide resin + 20℃

[0192] The prepared test specimens were left for 24 hours at a temperature of 23°C under a nitrogen atmosphere in accordance with ASTM D638. Then, a tensile test was performed in accordance with ASTM D638 under an atmosphere of 140°C to measure the tensile strength.

[0193] 3-2. Retention rate of tensile strength before and after mixing of copper-based heat stabilizers

[0194] The tensile strength at high temperature of a polyamide resin composition infused with a copper-based heat stabilizer was compared with the tensile strength at high temperature of a polyamide resin composition in which the amount of additives was equal except for the absence of the copper-based stabilizer, and the retention rate of tensile strength at high temperature before and after the infusion of the copper-based heat stabilizer was calculated.

[0195] 3-3. Tensile Strength (Initial)

[0196] The test specimen prepared above was left for 24 hours at a temperature of 23°C under a nitrogen atmosphere in accordance with ASTM D638. Then, a tensile test was performed in accordance with ASTM D638 under an atmosphere of 23°C at a temperature of 50% relative humidity to measure the tensile strength.

[0197] 3-4. Tensile Strength (After High-Temperature Treatment)

[0198] The test specimen prepared above was left at a temperature of 220°C for 1000 hours. Afterwards, the test specimen was cooled to 23°C, and a tensile test was performed in accordance with ASTM D638 under an atmosphere of 23°C and 50% relative humidity to measure the tensile strength.

[0199] 3-5. Retention Rate of Tensile Strength

[0200] The initial tensile strength and the tensile strength after high-temperature treatment were compared, and the ratio of the tensile strength after high-temperature treatment to the initial tensile strength (retention rate) was calculated.

[0201] 3-6. Flow Length

[0202] Each polyamide resin composition was injected under the following conditions using a bar flow mold with a width of 10 mm and a thickness of 0.5 mm, and the flow length (mm) of the polyamide resin composition within the mold was measured. Meanwhile, a longer flow length indicates better injection fluidity.

[0203] Molding machine: Manufactured by Toshiba Machine Corp., EC75N-2A

[0204] Injection setting pressure: 2000 kg / cm² 2

[0205] Molding machine cylinder temperature: 335℃

[0206] Mold temperature: 160℃

[0207] Table 1 shows the composition, fluidity, tensile strength (at high temperature), the retention rate of tensile strength before and after mixing with a copper-based heat stabilizer (at high temperature), tensile strength (initial), tensile strength (after high temperature treatment), and the retention rate of tensile strength of the prepared polyamide resin composition.

[0208]

[0209] As is evident from Table 1, a polyamide resin having a component unit (b2) derived from diamine represented by Formula (1) can suppress the decrease in tensile strength at high temperatures caused by the incorporation of a copper-based heat stabilizer (comparison between Example 1 and Comparative Example 2). In addition, a polyamide resin having a component unit (b2) derived from diamine represented by Formula (1) can suppress the decrease in mechanical strength under high temperature and high humidity environments.

[0210] Meanwhile, a resin composition was also prepared in the same manner as in Example 1, except that the polyamide resin was PA6T (diamine was HDMA 100 mol%), but it could not be evaluated because it could not be injection molded under the above conditions.

[0211] In addition, it was newly confirmed that when a heat stabilizer other than a copper-based heat stabilizer is added, a decrease in tensile strength or fluidity occurs after high-temperature treatment. However, in these cases, it can be seen that even if the above-mentioned polyamide resin is used in combination, the decrease in tensile strength or fluidity after high-temperature treatment cannot be sufficiently suppressed (comparison of Example 1 and Reference Examples 5 to 10). From this, it can be seen that by combining a polyamide resin having a component unit (b2) derived from diamine represented by formula (1) with a copper-based heat stabilizer, the decrease in fluidity can be suppressed while the decrease in mechanical strength under high temperature and high humidity environments can be suppressed.

[0212] The present application claims priority based on Japanese Patent Application No. 2022-003317 filed on January 12, 2022. All contents described in the specification of said application are incorporated by reference into the present specification. Industrial applicability

[0213] According to the polyamide resin composition of the present disclosure, it is possible to achieve both an improvement in mechanical strength by adding a copper-based heat stabilizer and the suppression of the decrease in tensile strength after high-temperature treatment. Therefore, the present disclosure is expected to broaden the applicability of polyamide resins for various applications and contribute to the further dissemination of polyamide resins.

Claims

Claim 1 A polyamide resin composition comprising a polyamide resin and a copper-based heat stabilizer, wherein the copper content of the copper-based heat stabilizer is 0.001 parts by mass or more and 0.050 parts by mass or less per 100 parts by mass of the polyamide resin, and the polyamide resin comprises a component unit (a) derived from a dicarboxylic acid and a component unit (b) derived from a diamine, wherein the component unit (a) derived from the dicarboxylic acid comprises a component unit (a1) derived from terephthalic acid, naphthalene dicarboxylic acid, or cyclohexane dicarboxylic acid in an amount of 45 mol% or more relative to the total moles of the component unit (a) derived from the dicarboxylic acid, and the component unit (b) derived from the diamine comprises a component derived from an alkylene diamine having 4 to 18 carbon atoms in an amount greater than 50 mol% and 90 mol% or less relative to the total moles of the component unit (b) derived from the diamine. A polyamide resin composition comprising a unit (b1) and a component unit (b2) derived from a diamine represented by the following formula (1), which is 10 mol% or more and less than 50 mol% with respect to the total moles of the component unit (b) derived from the diamine. (In Equation (1), m and n are each independently 0 or 1, and -X- is a single bond, or a divalent group selected from the group consisting of -O-, -S-, -SO2-, -CO- and -CH2-) Claim 2 In claim 1, the polyamide resin composition comprises a component unit (b2) derived from a diamine represented by the formula (1), wherein the polyamide resin comprises 15 mol% or more and less than 45 mol% with respect to the total moles of the component unit (b) derived from the diamine. Claim 3 A polyamide resin composition according to claim 1, wherein the component unit (b1) derived from an alkylene diamine having 4 to 18 carbon atoms comprises a component unit derived from a straight-chain alkylene diamine or a branched-chain alkylene diamine. Claim 4 A polyamide resin composition according to claim 3, wherein the straight-chain alkylene diamine or branched-chain alkylene diamine is a diamine selected from the group consisting of 1,4-diaminobutane, 1,6-diaminohexane, 1,9-noneneindiamine, 1,10-decanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine. Claim 5 delete Claim 6 A polyamide resin composition according to claim 1, wherein the melting point (Tm) of the polyamide resin is 280°C or higher. Claim 7 In claim 1, the polyamide resin is a crystalline polyamide resin, a polyamide resin composition. Claim 8 A polyamide resin composition according to claim 1, wherein the melting heat (ΔH) of the polyamide resin is 10 mJ / mg or more. Claim 9 A polyamide resin composition, which is a resin composition for a vehicle body according to any one of claims 1 to 4 and 6 to 8. Claim 10 A polyamide molded article comprising a polyamide resin composition described in any one of claims 1 to 4 and claims 6 to 8. Claim 11 In claim 10, a polyamide molded body which is a vehicle material.

Citation Information

Patent Citations

  • Semiaromatic polyamide, semiaromatic polyamide resin composition, and molded article

    KR1020150063498A

  • Heat-curable resin composition, polyamide, adhesive sheet, cured article, and printed wiring board

    KR1020170029527A